The VALIDITY OF NATURE-BASED WORKSHEET TO ENHANCE STUDENTS’ RESEARCH SKILL AND ENVIRONMENTAL AWARENESS - Balgis Az Zahra; Rini Solihat; Lilit Rusyati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research was aimed to produce Nature-Based Worksheet on Ecology Material at grade VII that could improve students’ research skill and environmental awareness. This research was a research and development by adopting procedure of four-D (4D) which was modified into 3D namely define, design, and development phase. The nature-based worksheet consisted of three main activities which are observation, research planning and research conduction. Validity instrument were correspondence with basic competence, content writing and grammar conformity and correspondence with nature-based learning aspect. The result of the research showed valid for relevancy with learning outcomes, suitability of content and grammar, and suitability of nature-based learning.